Recurso especial mediante a problemática distinção entre questão de fato e questão de direito - Bertoldi, Thiago Moraes (2011)
This study aims to identify the limits of the activity exercised in the Special Recourse, by the Superior Court of Justice, upon the problematic dichotomy matter of fact/matter of law. With assistance of the deductive method, the theme is treated in three segments. Primarily are ventilated more general and historical aspects related to the Special Recourse, and proceeded a delimitation of the institute. By sequence, the approach routes to the problematic distinguishing between matter of fact and matter of law, through the analysis of issues related to the theme and of its main theories in the seat of national and foreign doctrine. Finally, already defined the broader aspects of the research, we pass to the analysis of the Special Recourse and the fact-law dichotomy, remaining established that, being difficult to differentiate the questions in some cases, the problem must be faced, in Special Recourse, under the prism of preponderance, in other words, there will be matters predominantly of fact and matters predominantly of law. In cases involving vague content concepts, must be also considered the variable that the Superior Court of Justice may examine the Special Recourse under the standard of transcendence of the matter brought to its knowledge.